2013
DOI: 10.1075/lab.3.4.02ima
|View full text |Cite
|
Sign up to set email alerts
|

Gender agreement in L3 English by Basque/Spanish bilinguals

Abstract: This study investigates knowledge of the nominal agreement domain in L3 English by Basque/Spanish bilinguals. Gender agreement has been claimed to be an interpretable feature in English and could be claimed to be so for Basque, whereas Spanish shows uninterpretable gender agreement. Under current representational and computational accounts posited to explain variability in L2 learner production, interpretable features are acquirable. The participants in the present study (n=34) were Basque/Spanish bilinguals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…by Basque/Spanish bilinguals in a minimal input setting. Anecdotal evidence as well as a previous exploratory study on this topic (Imaz Agirre and García Mayo, 2013) showed the problems L3 English learners have establishing gender agreement between the possessor and the possessee, as in (1).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…by Basque/Spanish bilinguals in a minimal input setting. Anecdotal evidence as well as a previous exploratory study on this topic (Imaz Agirre and García Mayo, 2013) showed the problems L3 English learners have establishing gender agreement between the possessor and the possessee, as in (1).…”
Section: Introductionmentioning
confidence: 71%
“…with L2 Spanish (Sagarra and Herschensohn, 2011) completing online comprehension tasks have also reported this finding. Concerning the effect of the grammatical gender of the Spanish equivalent noun or 'gender attraction effects', previous research found these effects in the production of L2 and L3 English possessives (Imaz Agirre and García Mayo, 2013;Santesteban et al 2010).…”
Section: Summary Of Research Questions and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations